ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2006-2010) - Noviana, Sindi Retno; Yuyetta, Etna Nur Afri (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2011)
This study aims to analyse and examine empirically the factors that affect income smoothingpractice among manufacturing companies listed on the Indonesia Stock Exchange. Factorstested in this study are profitability, financial risk, firm value, managerial ownership, publicownership and dividend payout ratio. Data collection used a purposive sampling methodconducted on manufacturing companies listed on the Indonesia Stock Exchange in the period2006-2010. The hypothesis were tested using multiple regressions to examined the influenceof profitability, financial risk, firm value, managerial ownership, public ownership anddividend payout ratio toward income smoothing practice. The result of this study showed thatfinancial risk and dividend payout ratio has significant influence to income smoothing.Profitability, firm value, managerial ownership and public ownership did not have significantinfluence to income smoothing.Keywords:income smoothing, profitability, financial risk, firm value, managerial ownership, publicownership and dividend payout ratio.